MANAGEMENT OF TRAINING PROGRAMS BY HRD CV.SULTAN COFFEE INDONESIA - Bambang Septiawan (Universitas Islam Balitar, 2021)
This research focuses on investigating the management of training program which held by CV. Sultan Coffee Indonesia. Even though, this company still in process of developing since 2019, it needs to conduct training regularly to build up the excellent capacity to the employee for making sure the products follows market wants. The theories used are about human resource management focusing on developing good capacity for employee from several experts. The data is taken by observing, the secondary researcher is full observer that assist a lot for collecting the data. The analysis data is done sequently until find and describe the result as well as discussion of the research. The result finds that management training program starting with training needs assessment analysis, goal formulation, design, implementation, until training evaluation. Each step is done sequently according to the needs of training regularly or conditionally based on the requirement for gaining the highest market and profit.